Integration of Literature and Language: Teaching Lower-level Spanish Courses and the Academic Recovery of U.S. Hispanic Periodicals - M. Montserrat Feu López (Doblele, 2017)
This essay examines the possibilities and challenges of teaching literature in the Spanish language class. Considering the need to diversify content, this essay integrates humanistic objectives when describing the past with literary texts recovered from U.S. newspapers.